The effects of dollar exchange rate changes on the feasibility of projects in the Iraqi economy - Ali Abdulhussein Khaleel Alfadhel; Dr. HAYDER HAMMOODI ALI; Dr. WISAM NEMAH JAAFAR RAGEEB; Dr. Zainab Hadi Maaouf Al-Sharif (Zien Journals, 2023)
This research aims to know the change effect of dollar exchange rates on the Iraqi economy and its sectors and the feasibility of projects. It clarifies the problem of research in the extent to which the global economy and economic sectors in Iraq are affected by changes in dollar exchange rates, and whether these changes in the short term have negative effects or not. Will it affect the estimates made by consultants in calculating the feasibility of projects? The research time period was determined during the period between the years (2018-2022) due to what it witnessed from two global crises. The result of was the change in dollar exchange rates, which left an impact on the Iraqi economy. The research uses the descriptive and analytical approaches, through the analysis of statistical, financial and economic data during the research period, in order to obtain the results and analyze them economically. The study showed a clear impact as a result of the change in dollar exchange rates on the Iraqi economy during the short term. Also, there are many problems with the Iraqi system followed and must be repaired, and reformed in all sectors, including the sector of trade, transport, industry, health and medical sectors. There should be an appropriate study before taking any step towards changing the exchange rates of the dollar, whether rising or falling, especially in rentier countries, including Iraq
Keywords: Dollar exchange rates; Project feasibility